Aktivitas Antioksidan Ekstrak Air Kombinasi Kulit Pisang Kepok (Musa paradisiaca L.) dan Nanas (Ananas comosus L.) dengan Metode DPPH dan FRAP - Vivian Fu; Pratiwi Apridamayanti; Sri Luliana (Indonesian Journal of Pharmaceutical Education, 2023)
Banana kepok (Musa paradisiaca L.) and pineapple (Ananas comosus L.) are types of fruit that are widely consumed by the community. However, the skin is only disposed of as waste, where the waste of the fruit skin reaches 30% of the whole fruit. Kepok banana peels and pineapples contain phenols and flavonoids which are proven to function as antioxidants. This study aims to determine the IC50 value of the combined sample using the DPPH and FRAP methods. The extract samples were divided into 2 groups, namely the combination of kepok banana peel extract and pineapple with a ratio of 1:1 and 1:3. Extraction is done by infusion method. Analysis of the content of phenolic and flavonoid compounds was carried out by the TLC method on single samples of kepok banana peels and pineapple peels. Antioxidant activity test was carried out by 2 methods, namely DPPH and FRAP. The yield of the extract in the 1:1 combination was found to be 48% and the 1:3 combination was 47%. The chromatogram profile showed that each single sample was positive for phenols and flavonoids. The results of the analysis of the antioxidant activity of the DPPH method showed the IC50 value in the 1:1 combination group was 1188.27 ppm while in the 1:3 combination group it was 740.98 ppm. In the FRAP method, the IC50 value in the 1:1 combination group was 1251.85 ppm, while in the 1:3 combination group it was 2218.94 ppm. Based on the results of the test, there are differences in the measurement of antioxidant activity with 2 different methods based on the antioxidants action that contains in the sample, so that the more recommended method is DPPH based on the type of antioxidant compounds contained in the sample.